Optimization of the control loops of the variable frequency induction motor drive of the flame reactor feed screw - Dementyev, Yu.N.; Vajda, I.; Koyain, N.V.; Negodin, K.N.; Obraztsov, K.V. (EAI Endorsed Transactions on Energy Web, 2017)
In the paper the optimization of the control loops of the variable frequency induction motor drive for the feed screw of a flame reactor has been carried out to obtain required dynamic characteristics of the electric drive for known parameters of the plant. Simulation studies of basic control loops (current, flux-linkage and speed) are performed and dynamic parameters of control quality are presented. Results of the studies show that the obtained parameters meet requirements of the workflow and the modern variable-frequency drive based on induction motor can be implemented for actuating the feed screw of flame reactor. It should also be mentioned that transients quality factors in speed loop with input filter are better than without it.
Keywords: variable frequency induction motor; electric drive; optimization; control loop